Between masks and mirror – two self-portraits by Felix Nussbaum (Ars inspiratio: Studies dedicated to Professor Eleonora Jedlińska, 2024)
Felix Nussbaum was an artist whose years of creative activity coincided with the Weimar Republic and the Third Reich. This artist, extremely narrative in his art, is primarily associated with his politically-tinged works painted during the Second World War, which became poignant testimony to the Holocaust. However, Nussbaum himself opposed the categorisation of his artistic activities for quite a long time; nevertheless at the same time, in most of his pre-war works, he tried to subtly express his opinion on issues currently bothering him related to his perception of family, society and religion. In this article, I have undertaken an analysis of two self-portraits (Self-Portrait with a Mask and Self-Portrait at the Easel) to show how, in this painting genre, the artist sought answers underlying his shaky identity.